GPS Receiver Position Estimation and DOP Analysis Using a New Form of the Observation Matrix Approximations. (19th September 2022) - N, Ashok Kumar; Kumar, P. Sirish; Mohiddin, Md. Khaja; Gemeda, Mulugeta Tegegn; Mishra, Anup
Abstract : A location sensor is a feature that communicates with a Global Positioning System (GPS) receiver to learn about the status of the current location. This work presents the GPS receiver position estimation and Dilution of Precision (DOP) analysis using a new approximate form of observation matrix which can be used in place of the classic observation matrix that was derived from the Taylor's series. It has been realized that, the approximate observation matrix is numerically stable and provides greater precision in calculating DOP values and estimating the position of a GPS receiver. The experimental results show that the proposed observation matrix provides better precision in DOP analysis and GPS receiver position estimation with a fast convergence rate and improved algorithm stability. Therefore, it can be concluded that the proposed new observation matrix plays a significant role to estimate accurately the location of the GPS receiver position and to enhance all parameters of the DOP.